Colloidal Shaping of Transparent Spinel through Slip Casting Using Contamination Free Spinel Moulds. Issue 1 (2nd January 2022) - Singh, Shiv Prakash; Biswas, Papiya; Johnson, Roy
Abstract : Shaping transparent ceramics through slip casting on plaster of Paris (PoP) moulds offers improved transparency compared to compacted samples due to better homogeneity in colloidal processing. However, the contamination due to CaSO4 originated from the PoP contact is a primary concern. Therefore, it demands the machining of several layers from the cast surface that results in post-green machining defects. To address this concern, a magnesium aluminate (MgAl2 O4 ) spinel mould was fabricated with indigenously synthesized spinel powder with optimum porosity of 45-50% and flexural strength of ∼16 MPa. The fabricated spinel mould was used to demonstrate the casting using water-based spinel slurry. The cast spinel blanks were found contamination free as confirmed by Fourier transform infrared studies. Microstructures of spinel moulds revealed the interconnectivity of the pores obtained by field emission scanning electron microscopy. Specimens cast on spinel and on PoP moulds, after post machining, were sintered (1650°C) and hot isostatically pressed (at 1800°C and 1950 bar) under identical conditions. Casting on spinel moulds demonstrated a contamination free surface of the samples. Its properties are at par with the samples cast on PoP moulds, however, with improved casting rate and minimum rejection. GRAPHICAL ABSTRACT: UF0001